PENGATURAN PENGELOLAAN KONSERVASI KELAUTAN BERKELANJUTAN - Gatot Dwi Hendro Wibowo (Perspektif, 2005)
As archipelago state, Indonesia has biggest biological diversity of marine in the world. It needs a good manage and consider with the needs of present without compromising the ability of future generations to meet their own needs. The most important to realize this objective is a make regulation related with marine and coastal resources of law. The regulation must be consider with sustainable development principle especially precautionary principle and conservation on biological diversity principle.